Between Religion and Agriculture: A Roadmap to Revamping Nigeria’s Economy - Eyo, Ubong E. (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
This paper investigated “Between Religion and Agriculture: A Roadmap to Revamping Nigeria's Economy." Religion is meant to affect all facets of life both at the individual and community levels. This applies equally to the economy of nations including Nigeria as a sovereign state. Petroleum which has been Nigeria's mainstay economically over the past five decades has proved to be not a sustainable means of income to the country in recent times. With the fluctuation in oil price with its attendant nose-diving, Nigeria is bound to have a rethink over her means of economic stay. This informs the thrust of this paper which looks at revamping Nigeria's economy from a religious perspective. Using the creation accounts in Genesis Chapter one and two, this paper which looks at the original divine mandate given to humanity in the days of creation; it concludes that this economic mandate was agriculturally based. Hence, this paper, using the hermeneutical approach to the study of scripture and content analysis research methodology calls on all ecclesial bodies to promote the agricultural sector not only as of the way of revamping Nigeria's economy but as a positive response to the divine mandate. Apart from adding to the body of interpretations of the texts under review, the contribution of this paper to knowledge is its application of these texts to the Nigerian economy.